Existential Migration: Conceptualising out of the experiential depths of choosing to leave "home"* (Existential Analysis: Journal of the Society for Existential Analysis, 2006)
The following is a preliminary discussion of research that unexpectedly gave rise to the new concept of ‘existential migration’. Phenomenological interviews with voluntary migrants, individuals who choose to leave their homeland to become foreigners in a new culture, reveal consistently deep themes and motivations which could convincingly be labelled ‘existential’. Rather than migrating in search of employment, career advancement, or overall improved economic conditions, these voluntary migrants are seeking greater possibilities for self-actualising, exploring foreign cultures in order to assess their own identity, and ultimately grappling with issues of home and belonging in the world generally. The article offers a sketch of this phenomenon with reference to Martin Heidegger’s ontology, thereby indicating alternative understandings of ‘home’, ‘not-being-at-home’, ‘belonging’, which take into account the narratives of these migratory experiences. An example of the conceptual ramifications of this new understanding of voluntary migration is found in the definition of ‘home as interaction’ rather than the usual ‘home as place’. The article offers a cautionary note regarding the potentially profound and mostly ignored psychological consequences of the contemporary push to increasing globalisation. As a summary article, what follows will potentially raise more questions than answers for the reader; further articles will be forthcoming and feedback is welcome.
Keywords: Existential; Migration; Anthropology; Unheimlich; Heidegger; Globalisation; Home; Belonging; Acculturation; Cross-cultural Therapy.